Quantifying entanglement in a 68-billion-dimensional quantum state space - James Schneeloch (Nature Portfolio, 2019)
Quantifying entanglement in a large quantum system requires an intractable number of measurements. Here, the authors demonstrate a method for certifying entanglement from extremely undersampled data by combining a new quantitative entanglement witness with an adaptive sampling procedure.